The relationship between central bank auctions and bill market liquidity - Joost V. Bats; Jurian J. A. Hoondert (European Central Bank (ECB), 2022)
This paper investigates the relationship between central bank (reverse) auctions and bill market liquidity. The analysis includes data on the purchases of bills in the auctions by the Dutch Central Bank under the European Central Bank's Pandemic Emergency Purchase Programme (PEPP). The results indicate that auctions contribute to smooth market functioning. Two findings stand out. First, by purchasing bills using auctions rather than bilaterally, the central bank increases the bid-to-cover ratio at bill issuance, especially in times of stress. Second, bills are offered at larger sizes and lower prices in central bank auctions near primary issuance.
Keywords: E42; E44; E52; E58; G12; 330; Central bank auctions; bills; liquidity